2016
DOI: 10.1590/1806-93042016000100005
|View full text |Cite
|
Sign up to set email alerts
|

Nascimentos no Brasil: associação do tipo de parto com variáveis temporais e sociodemográficas

Abstract: Objectives: to identify caesarean and vaginal births and their association with temporal and sociodemographic variables.Methods: a mixed approach involving descriptive time series studies (2000, 2005, 2010) and one crosssectional study (2011) (2000, 2005, 2010)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
1
51

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 9 publications
4
30
1
51
Order By: Relevance
“…The results found are alarming when compared to the ones observed as in a national level, 43.89% 10 and 53.7%, 17 as in other Brazilian studies [11][12][13]16 which ranged from 31.1% 12 to 56.3%. 13 However, the proportion of cesarean sections found in this study, corroborates with the proportions identified in 2012 and 2013 in the South Region and were circulated recently by the Ministry of Health, 62% and 62.7%, respectively.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gracontrasting
confidence: 61%
See 3 more Smart Citations
“…The results found are alarming when compared to the ones observed as in a national level, 43.89% 10 and 53.7%, 17 as in other Brazilian studies [11][12][13]16 which ranged from 31.1% 12 to 56.3%. 13 However, the proportion of cesarean sections found in this study, corroborates with the proportions identified in 2012 and 2013 in the South Region and were circulated recently by the Ministry of Health, 62% and 62.7%, respectively.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gracontrasting
confidence: 61%
“…19 The authors presume that living in rich regions in the country, as the South Region, it favors the use of private health services, which have high rates of cesarean sections, between 80% and 90%. 17 This observation seems to be in favor with the findings of this study, in which the identified region with the highest proportion of cesarean sections was the CRS in Palmeira das Missões, in the North Region, which stood out as the third highest Socioeconomic Development Rate in the State (0.795). 20 The results suggest that a cesarean section may be associated to a better socioeconomic condition of the population.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gramentioning
confidence: 62%
See 2 more Smart Citations
“…With regard to the mothers' age, a study reports that the proportion of births via C-section was from 60% to 70% among women older than 30 years of age, 21 which may be related to fear as older women are more predisposed to risk during pregnancy. Age is seen as a risk factor for some morbidities during pregnancy and may be a relevant factor at the time women decide on the route of delivery, though such a conjecture cannot be confirmed.…”
mentioning
confidence: 99%